Phase II clinical study of erlotinib for treatment of myelodysplastic syndromes. Issue 8 (16th May 2014) - Komrokji, Rami S.; Padron, Eric; Yu, Daohai; Fulp, William J.; Rodriguez, Yuraima; Tinsley, Sara; List, Alan F.; Lancet, Jeffrey E.
<x xml:space="preserve">Abstract</x> Outcome in patients with myelodysplastic syndrome (MDS) after azanucleoside failure is poor with unmet need for active novel agents. Preclinical data have suggested that erlotinib has in vivo and in vitro off epidermal growth factor receptor (EGFR)‐target activity in MDS. We conducted a phase II study with single‐agent erlotinib 150 mg/day orally in MDS patients following azanucleoside failure. All intermediate‐2 or high‐risk MDS patients by International Prognostic Scoring System and only those low/intermediate‐1 patients with transfusion‐dependent anemia or platelet counts <50 × 109/L or a significant clinical hemorrhage requiring platelet transfusion or ANC <1 × 109/L were eligible, with most of our patients being at high risk. In 35 eligible patients, overall best response was 14% (3 patients having marrow complete response and 2 hematological improvement). Four deaths occurred on study (sepsis, intracranial hemorrhage, sudden death, and acute myeloid leukemia (AML)). The most common observed grade 3/4 toxicities according to CTCAE v3 were diarrhea (17.1%), rash (17.1%), and infection (11.6%), accompanied by fatigue, thrombocytopenia, and anorexia at 5.7% each. Median overall survival was 6.8 months (95% CI 4.9–13.2), and leukemia‐free survival was 5 months (95% CI 3.4–7.3). Erlotinib was generally well tolerated, with modest single‐agent activity. Given these results and preclinical data suggesting synergistic effect with azanucleosides, the combination should be further explored. Am. J. Hematol. 89:809–812, 2014. © 2014 Wiley Periodicals, Inc.